A novel reassortant influenza A (H1N1) virus infection in swine in Shandong Province, eastern China. Issue 1 (27th September 2019) - Yu, Zhijun; Cheng, Kaihui; He, Hongbin; Wu, Jiaqiang
Abstract: Influenza A (H1N1) viruses are distributed worldwide and pose a threat to public health. Swine, as a natural host and mixing vessel of influenza A (H1N1) virus, play a critical role in the transmission of this virus to humans. Furthermore, swine influenza A (H1N1) viruses have provided all eight genes or some genes to the genomes of influenza strains that historically have caused human pandemics. Hence, persistent surveillance of influenza A (H1N1) virus in swine herds could contribute to the prevention and control of this virus. Here, we report a novel reassortant influenza A (H1N1) virus generated by reassortment between 2009 pandemic H1N1 viruses and swine viruses. We also found that this virus is prevalent in swine herds in Shandong Province, eastern China. Our findings suggest that surveillance of the emergence of the novel reassortant influenza A (H1N1) virus in swine is imperative.